Kantocu Women in Tulûat Theater in Istanbul between 1880-1920 - Dila Okuş (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
Kanto is a stage performance that became significantly popular in 19th-century Istanbul. Kanto may also formally be defined as an actress singing and dancing on stage. Kanto performances gained the attention of many people, and big fan groups gathered around kanto artists. Meanwhile, some groups described kanto as a light banal type of performance and accused these women singers of being meretricious as they stood on stage behaving flirtatiously. The criticisms directed at the kanto performances and artists stemmed from the cultural context that had shaped the Ottoman society of the period. This study will analyze women’s kanto performances between 1880-1920 in tulûat [improvisational] theater with regard to the performance tools and social-cultural context surrounding the artists. The study will discuss the biographies and works of leading names in kanto such as Peruz Terzekyan, Şamram Kelleciyan, Küçük Virjin, and Amelya in terms of the commonly encountered aspects and will reveal the effects artists’ female identities had on kanto’s performance and reception.